2019
DOI: 10.1055/s-0039-1691528
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oxidative Dearomatization of Indoles with Aromatic Ketones: Rapid Access to 2,2-Disubstituted Indolin-3-ones

Abstract: A metal-free oxidative dearomatization of indoles with aromatic ketones mediated by TEMPO oxoammonium salt is described. The dearomatization proceeds smoothly and displays a broad substrate scope with respect to both indoles and aromatic ketones in the presence of H2SO4, affording the corresponding 2,2-disubstituted indolin-3-ones in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The Liu group has recently reported a TEMPO oxoammonium salt‐mediated oxidative dearomatization of indoles 56 with aromatic ketones 57 in the presence of H 2 SO 4 (Scheme 23). [31] This metal‐free dearomatization reaction proceeded smoothly and tolerated a broad substrate scope, including a number of indoles and aromatic ketones, leading to the desired 2,2‐disubstituted indolin‐3‐ones 58 in good yields. This method built a novel path for the subsequent research on ketones involving dearomatization.…”
Section: Oxidative Dearomatization Reactionsmentioning
confidence: 90%
“…The Liu group has recently reported a TEMPO oxoammonium salt‐mediated oxidative dearomatization of indoles 56 with aromatic ketones 57 in the presence of H 2 SO 4 (Scheme 23). [31] This metal‐free dearomatization reaction proceeded smoothly and tolerated a broad substrate scope, including a number of indoles and aromatic ketones, leading to the desired 2,2‐disubstituted indolin‐3‐ones 58 in good yields. This method built a novel path for the subsequent research on ketones involving dearomatization.…”
Section: Oxidative Dearomatization Reactionsmentioning
confidence: 90%
“…Liu and colleagues (Table 1, R) described a metal-free oxidative dearomatization of indoles with aromatic ketones through the use of TEMPO oxoammonium salt. 21 In the presence of H2SO4, the dearomatization went without a hitch and demonstrated a broad substrate range with respect to both indoles and aromatic ketones, producing the matching 2,2-disubstituted indolin-3-ones in good yields. A completely metal-free catalyst system was created for the selective aerobic oxidation of structurally varied benzylic sp 3 C-H bonds of ethers and alkylarenes.…”
Section: Template For Synopen Thiemementioning
confidence: 99%
“…190 Later, Zhu, and Liu et al reported a similar Brønsted acid-mediated similar racemic transformation. 191 3-6-3. Oxidation of furan (Scheme 31)…”
Section: -6-1 Oxidation Of Phenolsmentioning
confidence: 99%